Rancang Bangun Aplikasi Penapisan Calon Akseptor KB Berbasis Android “Tapis Yuk” - Astri Nurdiana (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2020)
Midwives hold an essential role in providing family planning services, therefore it has to be appropriate and in accordance with the condition of prospective family planning acceptors. Every contraception service is needs to begin by family planning screening of acceptors, selecting the right and appropriate type of contraception could affect the women’s welfare and health in the future. The smartphones use is currently grow rapidly, as evidenced by the infographic of Indonesian smartphone users in 2019 reaching 355.5 million. In Indonesia, smartphones with the Android operating system are the largest market for use compared to other smartphone operating systems. The combination of the family planning service needs along with technology developments led to the idea of ​​creating an Android-based family planning contraception screening application called